2019
DOI: 10.1007/s10591-019-09491-z
|View full text |Cite
|
Sign up to set email alerts
|

To Navigate the Normative and the Not-Normative Family Therapists Negotiating Their Professional Identities with Parents Whose Children are Placed in Public Care

Abstract: This article negotiates family therapists´ professional identities in the Family Counselling Services (FCS) in Norway and their experiences when following up parents whose children are placed in public care. A qualitative study following seven family therapists in the FCS, through focus groups and individual interviews, found that they struggle with contradictory positions within their professional identity when following up with these parents. This struggle involves a dichotomy between their personal feelings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The reports from counsellors that these relationships were often fragile or problematic are worrying. It has often been highlighted in the literature (see, for example, Cox, McPherson and Blumenfeld, 2021; Syrstad and Ness, 2019) that the material realities of birth relatives’ lives can have a determining impact on whether therapeutic intervention can be established, sustained and of use. Therefore, attending to matters such as benefit claims, housing, employment, contact with the child, Letterbox contact and relationships with social services should be defined as part of the practitioner’s role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reports from counsellors that these relationships were often fragile or problematic are worrying. It has often been highlighted in the literature (see, for example, Cox, McPherson and Blumenfeld, 2021; Syrstad and Ness, 2019) that the material realities of birth relatives’ lives can have a determining impact on whether therapeutic intervention can be established, sustained and of use. Therefore, attending to matters such as benefit claims, housing, employment, contact with the child, Letterbox contact and relationships with social services should be defined as part of the practitioner’s role.…”
Section: Discussionmentioning
confidence: 99%
“…Syrstad and Slettebø (2019) have highlighted the importance of allowing birth parents to be something other than deviant individuals or failing parents – this can reduce shame and foster collaboration rather than defensiveness and resistance. Focusing on birth relatives’ strengths and abilities, including in their parenting identity, has been highlighted as one way to do this (e.g., Boddy et al., 2014; Syrstad and Ness, 2019). Furthermore, the idea of ‘bending the frame’ of counselling (Morgan et al., 2019) to disrupt the power differences and foster relational reciprocity and ease captures the stance the counsellors aimed to adopt.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it can also be understood as a manifestation of dysfunctional communication between parents and CPS (Höjer, 2011;Sykes, 2011). This type of collaboration can be understood as a form of power over, as described by Dumbrill (2006), and could further contribute to limiting parents' meaning-making process with caseworkers in which parents will be left feeling inadequate and disempowered (Syrstad and Ness, 2019). In such situations, Dumbrill (2006) observed that parents tended to either fight against the perceived authority or enter into collaboration with it because they found it useless to fight.…”
Section: Using Systemic Family Therapy Approaches In a Context Of Power Imbalancementioning
confidence: 99%